On the Utopian Possibility in Ursula K. Le Guin’s The Dispossessed: A Lacanian Reading - Murat Kabak (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
Written in 1974, the American writer Ursula K. Le Guin’s The Dispossessed revolves around the central character Shevek’s self-appointed mission to improve the relationship between two planets, Anarres and Urras, by breaking down the walls that are separating these ideological enemies. The novel, in that sense, can be read as one man’s search for an ideal state, rather than a description of a utopian/anti-utopian state. Literary scholars generally focus on various aspects of The Dispossessed in terms of its anarchist politics, ecological politics, and revolutionary politics. This article; however, aims to approach the novel from a Lacanian perspective by addressing the protagonist’s psyche and his relation to the socio-symbolic orders in the novel. By focusing on the characterization of the relations between the subject and the other in an anarchist (as well as a capitalist culture) in The Dispossessed, this article aims to analyze how the novel provides a path towards an ideal state.